The Exchange rate cycle in Argentina - Nicolini Llosa, Jose Luis (2016)
This article discusses the secular volatility of output, inflation, the exchange rate, and poverty in Argentina. Inflation, currency devaluation and a wide gross domestic product (GDP) cycle have been recurrent problems in Argentina for several decades. The literature has extensively discussed those issues from different viewpoints. This study focuses on a relatively unexplored theme that may contribute to a partial explanation. It deals with the continuous tendency to equalize different profitabilities resulting, in turn, from remarkably different sectoral purchasing power parities. Thus, for any given exchange rate, an incessant tendency toward the equalization of profitabilities generates opposing inflationary and devaluatory pressures. The resulting inflation-devaluation cycle feeds income redistribution, GDP fluctuation, real exchange rate instability, and high levels of uncertainty.